FRI0084 THE IMPACT OF IL-6 AND TNF INHIBITORS ON HEMOGLOBIN LEVELS: AN ANALYSIS FROM RHUMADATA® CLINICAL DATABASE AND REGISTRY. (June 2019) - Choquette, Denis; Bessette, Louis; Sauvageau, Loïc Choquette; Ferdinand, Isabelle; Haraoui, Paul; Massicotte, Frédéric; Pelletier, Jean-Pierre; Raynauld, Jean-Pierre; Rémillard, Marie-Anaïs; Sauvageau, Diane; Villeneuve, Édith; Coupal, Louis
Abstract : Background: Anemia is a common feature of RA. Prior to the appearance of biologic treatments, improvement of hemoglobin (Hb) levels was unusual and inconsistent. With better control of the inflammatory process with cytokine inhibitors, it has been shown that Hb levels can improve substantially. Recently in the development of IL-6 receptor antagonists (sarilumab (SARI) and tocilizumab (TOCI)) data have shown improvement in Hb levels related to the down-regulation of hepcidin. No direct comparison of Hb levels between TNF and IL-6 inhibition has been explored in observational data (1). Objectives: This analysis compares the impact of TNF and IL-6 inhibitors on Hb levels over time. Methods: Data collected since January 1, 2015 (when TOCI and SARI were available in Canada) at the Institut de Recherche en Rhumatologie de Montréal (IRRM) and the Centre de l'Ostéoporose et de Rhumatologie de Québec (CORQ) was extracted from the Rhumadata® clinical database and registry on January 7, 2019. Selected patients were those initiated on an IL-6 antagonist or a TNFi (adalimumab, certolizumab, etanercept, golimumab or infliximab) and had been treated for at least one year. Furthermore, patients were cancer free and had no diagnosis of Crohn's disease or ulcerative colitis and had creatinine (Cr) and ALT levels within the normal sex-specific range. IL-6 patients were matched (ratio 1:2) to TNFi patients based on age at treatment initiation, gender and baseline Hb. The collected data include baseline characteristics (socio-demographic variables, concomitant and past medication, comorbidities and the Charlson comorbidity index (CCI)), variables measured over time (Hb and other laboratory test results, patient and physician-reported outcomes, and disease activity measures such as CDAI and DAS28(4)-ESR. The groups were compared to identify potential confounder. Results: A total of 145 patients initiating an IL-6 antagonist since January 1, 2015 were matched with 286 patients prescribed a TNF inhibitor during the same time-period. Most patients were women (86%), the mean age at treatment initiation was 54.1 (standard deviation=11.7) years, and 16% were smokers. Baseline patient global, pain and fatigue assessments, made on a visual analogue scale ranging from 1 to 10, were 5.4 (2.5), 6.1 (2.5) and 5.5 (3.0) in the IL6 group and 5.1 (2.7), 5.5 (3.0) and 5.0 (3.2) in the TNFi group. Baseline disease activity was assessed as moderate or high/severe in 85.5% (IL6) and 85.9% (TNFi) of patients (DAS28(4)-ESR criteria). At treatment initiation, mean Hb level was 126.6 (12.4) g/L, and Cr and ALT levels were 66.2 (11.5) umol/L and 18.7 (6.5) U/L in the IL6 group and 67.0 (12.0) umol/L and 19.3 (6.8) U/L in the TNFi group. At three months, Hb had increased by 5.4 (10.2) g/L in the IL6 group and by 1.8 (13.9) g/L in the TNFi group (p-value=0.024). These respective changes at 12 months were 8.7 (11.4) g/L and 5.4 (9.2) g/L (p-value=0.042). Conclusion: This analysis confirms that IL-6 inhibition provides a numerically and statistically superior increase in Hb over TNFi. Reference: [1] Song, et al. Arthritis Research & Therapy 2013, 15:R141 Disclosure of Interests: Denis Choquette Grant/research support from: Abbvie, Amgen, Eli Lilly, Novartis, Pfizer, Sandoz, Consultant for: Abbvie, Amgen, Eli Lilly, Novartis, Pfizer, Sandoz, Speakers bureau: Abbvie, Amgen, Eli Lilly, Novartis, Pfizer, Sandoz, Louis Bessette Grant/research support from: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Eli Lilly, Janssen, Novartis, Pfizer Inc, Roche, Sanofi, UCB, Consultant for: AbbVie, Celgene, Eli Lilly, Novartis, Pfizer Inc, Loïc Choquette Sauvageau: None declared, Isabelle Ferdinand Consultant for: AbbVie, Amgen, Novartis, Pfizer, Speakers bureau: Amgen, Pfizer, Paul Haraoui Grant/research support from: Abbvie, Amgen, Pfizer, UCB, Consultant for: Abbvie, Amgen, Lilly, Pfizer, Sandoz, UCB, Speakers bureau: Pfizer, Frédéric Massicotte Consultant for: AbbVie, Pfizer, Janssen, Eli Lilly, Speakers bureau: Janssen, Jean-Pierre Pelletier Shareholder of: Shareholder in ArthroLab Inc., Grant/research support from: Study funded by TRB Chemedica SA, Consultant for: TRB Chemedica SA, Jean-Pierre Raynauld Consultant for: ArthroLab Inc., Marie-Anaïs Rémillard Consultant for: Abbvie, Amgen, Eli Lilly, Novartis, Pfizer, Sandoz, Paid instructor for: Abbvie, Amgen, Eli Lilly, Novartis, Pfizer, Sandoz, Speakers bureau: Abbvie, Amgen, Eli Lilly, Novartis, Pfizer, Sandoz, Diane Sauvageau: None declared, Édith Villeneuve Consultant for: AbbVie, UCB, Celgene, Roche, Pfizer, Amgen, BMS, Sanofi-Genzyme, Paid instructor for: AbbVie, Speakers bureau: AbbVie, Pfizer, BMS, Roche, Louis Coupal: None declared